The possible protective effects of saccharum officinarum l. (sugar cane) juice co-supplementation on gentamicin induced acute renal toxicity in adult albino rats - Y. A. Hussein, Asmaa; Shaban EL-Shafey, Rabab (International Journal of Pharmacology and Toxicology, 2019)
Gentamicin (GM) is an effective and probably the most commonly used aminoglycosides antibiotic, however the risk of causing nephrotoxicity limits its use. In the present study, the possible protective effects of Saccharum officinarum L. (sugar cane juice) on gentamicin induced acute oxidative renal injury in experimental rats were investigated. Twenty adult albino rats were randomly allocated into four groups (5 rats in each) and treated once daily for a period of 7 days as follows; group A being the negative control and was injected intraperitoneal with normal saline, group B (sugar cane juice treated group) was given sugar cane juice orally at a dose of 15 ml/kg/day, group C (GM treated group) and group D (sugar cane juice + GM treated group) were the experimental groups and were injected intraperitoneal with (80 mg/kg/day GM) & (sugar cane juice 15 ml/kg/day orally + 80 mg/kg/day GM intraperitoneal) respectively. By the end of the experiment, the biochemical kidney functions tests (urinary cystatin C and kidney injury molecule-1, blood urea and creatinine) were investigated. Also, oxidative stress parameters (malondialdehyde [MDA] level, superoxide dismutase [SOD] & glutathione peroxidase [GPX] enzymatic activity) in renal tissue were evaluated. Histopathological examinations of kidney were done to assess the degree of renal protection induced by sugarcane juice, Gentamicin treated rats showed; marked significant rise in the biochemical kidney functions tests and lipid peroxidation (MDA) parameter in renal tissues, along with significant reduction in renal tissue antioxidant enzymatic activity of both SOD & GPX. However, co-administration of sugar cane juice in group D leading to marked reduction in previous biochemical markers and MDA levels together with significant elevated renal SOD &GPX enzymatic activity which nearly tend to return to normal values. The histopathological examination of groups A and B showed normal kidney structure which was deranged in group C (GM treated), whereas group D showed significant recovery in histological structures. Gentamicin induced acute renal injury and oxidative damage. Co-administration of sugar cane juice may reduce this damage by improving antioxidant defense and tissue integrity in experimental albino rats.Â Â Â